Hydrogen-Rich Saline Alleviates Kidney Fibrosis Following AKI and Retains Klotho Expression - Chen, Jing; Zhang, Han; Hu, Jiachang; Gu, Yulu; Shen, Ziyan; Xu, Linghan; Jia, Xueqi; Zhang, Xiaoyan; Ding, Xiaoqiang (Frontiers in Pharmacology, 2017)
Purpose: Acute kidney injury (AKI) is a prominent risk factor to develop chronic kidney disease (CKD). To date, the related mechanism and effective therapy have not been rigorously explored. The present study aims to explore the role of hydrogen-rich saline (HRS) in protecting kidney from AKI after ischemia/reperfusion (IR) injury. Methods: Adult male C57 mice were randomly allocated into three groups: sham, IR, IR+HRS. Renal IR injury model was generated via 35 min occlusion of double kidney pedicles, and then, according to different groups, mice were administered with different treatements intraperitoneally. After 14- or 28-day treatment, mice were perfused and the kidney were collected following reperfusion. Many moleculars were detected by western blots to investigate the functions of the kidney, including renal fibrotic proteins (a-smooth muscle actin (a-SMA), collagen Ⅰ(ColⅠ)), Klotho, the methylation of Klotho, damage-regulated autophagy modulator (Becline-1), and microtubule-associated protein light 3-II (LC3- II). Finally, Serum blood urea nitrogen (BUN) and creatinine (Cr) levels were measured. Results: Histological data showed that the HRS treatment significantly decreased fibrosis in renal tissues, in comparison with IR treatment. The changes in the expression of fibrotic markers, a-SMA and ColⅠ, were consistent with Trichrome staining, which showed a robust increase in IR injury models. IR injury enhanced LC3- II and Beclin-1 amounts, while decreasing Klotho levels. The Klotho level was alleviated by HRS, but LC3- II and Beclin-1 were starkly enhanced in HRS group. In addition, BUN and Cr were decreased in the HRS group than IR group. Conclusions: HRS showed a protective effect in the prevention of renal injury and could inhibit renal fibrosis after IR injury in mice. This role of HRS might be exerted via retaining Klotho expression and activating autophagy in kidney.